George Henry Dern papers - Dern, George Henry, 1872-1936.
Correspondence, memoranda, speeches, radio addresses, photographs, and other papers relating chiefly to Dern's service as U.S. secretary of war under Franklin D. Roosevelt. Documents inspection trips to the Mississippi River and the Saint Lawrence Seaway, formal and ceremonial occasions such as the 1933 Governor's Conference in California, and trips to Panama and the Philippines.
U.S. secretary of war and governor of Utah.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Roosevelt, Franklin D. -- 1882-1945.; United States. -- War Department; Governors -- United States; Mississippi River -- Description and travel; Panama -- Description and travel; Philippines -- Description and travel; Saint Lawrence Seaway -- Description and travel; Cabinet officers; Governors -- Utah